The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.wneu.2018.01.184
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Statins for Patients with Aneurysmal Subarachnoid Hemorrhage: Meta-Regression Analysis

Abstract: The present meta-regression provides weak evidence for dose-dependent reductions in vasospasm, DIND and mortality associated with acute statin use after aneurysmal subarachnoid hemorrhage. However, the analysis was limited by substantial heterogeneity among individual studies. Greater dosing strategies are a potential consideration for future RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Even with a big sample size, Kirkpatrick et al couldn't prove a statistical effect of simvastatin with a dose of 40 mg per day. Similarly, a meta regression found a dose-dependent reduction in DIND with acute statin in aSAH [47].Early administration of statin within 48 to 72 hours showed in subgrouping analysis a signi cant bene t in patients with aSAH, in compared to within 96 hours. In addition to, a duration of 14 days was signi cant than a duration of 21 days in subgrouping meta-analysis.…”
Section: Discussionmentioning
confidence: 88%
“…Even with a big sample size, Kirkpatrick et al couldn't prove a statistical effect of simvastatin with a dose of 40 mg per day. Similarly, a meta regression found a dose-dependent reduction in DIND with acute statin in aSAH [47].Early administration of statin within 48 to 72 hours showed in subgrouping analysis a signi cant bene t in patients with aSAH, in compared to within 96 hours. In addition to, a duration of 14 days was signi cant than a duration of 21 days in subgrouping meta-analysis.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, not only the type of statin but also its dose could be important for its effect on VS and outcome. A meta-analysis found weak evidence that a higher total statin dose reduced the risk for VS, DIND, and mortality [ 52 ]. They reported heterogeneity among the individual studies and suggested a better dosing strategy in future RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Preload with statins, i.e., pre-ictal statin use may have a different effect on the development of VS and outcome than initiation of statins at ictus as some studies found that the length and dose of administration were crucial for the effect of statins [52]. Some studies have investigated the effect of pre-ictal statin use on VS and outcome [36,40]; however, these were underpowered with regard to the number of statin users (all less than 50 patients) and hence failed to detect a significant impact on VS or outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This timepoint of drug administration differed from the latest clinical trials but was applied in a previous pilot trial. In a meta-regression analysis, there was weak evidence supporting a dose-dependent reduction in cerebral vasospasm, delayed cerebral ischemia, and mortality associated with the application of statin after SAH [ 91 ]. Simvastatin application of 40mg or 80mg per day within 96 hours after SAH was proven to be ineffective in improving delayed cerebral ischemia and clinical outcome, but the potential benefits of statin treatment cannot be dismissed.…”
Section: Introductionmentioning
confidence: 99%